How participatory processes impact children and contribute to planning: a case study of neighborhood design from Boulder, Colorado, USA. Issue Volume 10:Issues 1(2017) (2nd January 2017) - Derr, Victoria; Kovács, Ildikó G.
Abstract: Young people have much to offer urban planning, yet are not often included in such processes. A unique partnership in Boulder, Colorado, provides a venue for young people's participation in city planning. Boulder is in many ways a learning laboratory with progressive ideals and sustainability thinking. As the city began planning for its Comprehensive Housing Strategy, tensions about the future of density within the city emerged. Participatory planning can have significant impacts on children and can also contribute new ideas to planning processes. In this study, young people demonstrated attitudinal changes toward government, increased recognition of diverse needs within a city, and integration of social and environmental sustainability into their recommendations for neighborhood planning.